2006
DOI: 10.1002/ajmg.b.30324
|View full text |Cite
|
Sign up to set email alerts
|

Three major haplotypes of the β2 adrenergic receptor define psychological profile, blood pressure, and the risk for development of a common musculoskeletal pain disorder

Abstract: Adrenergic receptor β 2 (ADRB2) is a primary target for epinephrine. It plays a critical role in mediating physiological and psychological responses to environmental stressors. Thus, functional genetic variants of ADRB2 will be associated with a complex array of psychological and physiological phenotypes. These genetic variants should also interact with environmental factors such as physical or emotional stress to produce a phenotype vulnerable to pathological states. In this study, we determined whether commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
130
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 65 publications
7
130
0
2
Order By: Relevance
“…We previously identified polymorphisms in the COMT gene that are associated with low COMT enzymatic activity and TMJD onset (Diatchenko et al 2005). Here, we report the mechanism whereby low levels of COMT lead to exacerbated pain states.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We previously identified polymorphisms in the COMT gene that are associated with low COMT enzymatic activity and TMJD onset (Diatchenko et al 2005). Here, we report the mechanism whereby low levels of COMT lead to exacerbated pain states.…”
Section: Discussionmentioning
confidence: 81%
“…Our group demonstrated that human genetic variants of COMT are predictive for the development of Temporomandibular Joint Disorder (TMJD) and are associated with heightened experimental pain sensitivity (Diatchenko et al 2005). Variants associated with heightened pain sensitivity produce lower COMT activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their heuristic model, haplotype 2 is related to high expression of ␤ 2 -AR in the synaptic cleft and to inefficient internalization of such receptors in response to agonist stimulation. Their longitudinal observation demonstrated that healthy women with this haplotype 2 have a higher risk of developing TMJ syndrome (12).…”
Section: Discussionmentioning
confidence: 99%
“…While exposure to bullying in the workplace is a risk factor for pain (10,11), pain may also be determined by the individuals psychological profile and genetic susceptibility (12). Interestingly, as much as 60% (range 25-60%) of the variance in experimental pain may be explained by genetic variability (13).…”
mentioning
confidence: 99%